Neurocognitive Performance Deficits Related to Immediate and Acute Blast Overpressure Exposure - LaValle, Christina R.; Carr, Walter S.; Egnoto, Michael J.; Misistia, Anthony C.; Salib, Jonathan E.; Ramos, Alejandro N.; Kamimori, Gary H. (Frontiers in Neurology, 2019)
Addressing the concerns surrounding blast injury for the military community is a pressing matter. Specifically, sub-concussive blast effects, or those blast effects which do not yield a medical diagnosis but can result in symptom reporting and negative self-reported outcomes, are becoming increasingly important. This work evaluates explosive blast overpressure and impulse effects at the sub-concussive level on neurocognitive performance assessed with the Defense Automated Neurobehavioral Assessment (DANA) across seven breacher training courses conducted by the US Military. The results reported here come from 202 healthy, male military volunteer participants. Findings indicate that the neurocognitive task appearing most sensitive to identifying performance change is the DANA Procedural Reaction Time (PRT) subtask which may involve a sufficient level of challenge to reliably detect a small, transient cognitive impairment among a healthy undiagnosed population. The blast characteristic that was consistently associated with performance change was peak overpressure. Overall, this study provides evidence that increasing blast overpressure, defined as peak overpressure experienced in a training day, can lead to transient degradations in neurocognitive performance as seen on the DANA PRT subtask, which may generalize to other capabilities.